2016
DOI: 10.1080/15592324.2016.1217375
|View full text |Cite
|
Sign up to set email alerts
|

Pollen aquaporins: What are they there for?

Abstract: In order to provide more insight into the function of aquaporins during pollination, we characterized NIP4;1 and NIP4;2, 2 pollen-specific aquaporins of Arabidopsis thaliana. NIP4;1 and NIP4;2 displayed high amino acid identity. RT-PCR and GUS promoter analysis showed that they have different expression patterns. NIP4;1 is expressed at low levels in mature pollen, while NIP4;2 is highly expressed only during pollen tube growth. Single T-DNA nip4;1 and nip4;2 mutants and double amiRNA nip4;1 nip4;2 knockdowns s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Reductions in the expression of AtNIP4;1 and AtNIP4;2 by RNAi markedly inhibit pollen germination and pollen tube elongation, and decrease seed fertility. Further studies showed that the water permeable activities of AtNIP4;1 and AtNIP4;2 are regulated by phosphorylation at Ser-267 of the C termini by a pollen-specific calcium-dependent protein kinase 34 [ 127 , 143 ] ( Figure 3 c). Thus, the kinase-modulated AtNIP4;1 and AtNIP4;2 are important for pollen germination and pollen tube elongation.…”
Section: Roles Of Aqps In Reproductive Development Seed Developmementioning
confidence: 99%
“…Reductions in the expression of AtNIP4;1 and AtNIP4;2 by RNAi markedly inhibit pollen germination and pollen tube elongation, and decrease seed fertility. Further studies showed that the water permeable activities of AtNIP4;1 and AtNIP4;2 are regulated by phosphorylation at Ser-267 of the C termini by a pollen-specific calcium-dependent protein kinase 34 [ 127 , 143 ] ( Figure 3 c). Thus, the kinase-modulated AtNIP4;1 and AtNIP4;2 are important for pollen germination and pollen tube elongation.…”
Section: Roles Of Aqps In Reproductive Development Seed Developmementioning
confidence: 99%
“…In pollen grains, aquaporins play a role in mobilizing soluble carbohydrates, proline and interconverting enzymes between the vegetative and generative cells. This is important for maintaining pollen viability in response to environmental conditions (Kononowicz et al, 1992; Bots et al, 2005b; Anil Kumar et al, 2015; Pérez Di Giorgio, 2016). Similar to drought and other abiotic stresses, protection against reactive oxygen species (ROS) is activated and mitochondrial activity is decreased.…”
Section: Pollen Desiccation and Its Relationship To Sporophytic Drougmentioning
confidence: 99%
“…However their presence and expression may vary among plant species, tissues and time during development. In plants, AQPs are present in almost all organs, including the roots, leaves, stems, flowers, fruits, seeds, dry seeds [60], pollen [13,[61][62][63], anther and specific cells such as the guard cells [64,65]. Moreover, some TIPs are expressed in specific tissues, e.g.…”
Section: Study Of the Tissue-and Developmental-dependent Expression Omentioning
confidence: 99%